Attitudinal meaning in the syllabus of same-sex marriage legal document of the United States: a systemic functional linguistics approach - Ayu Pratiwi Ulfah; Eva Tuckyta Sari Sujatna; Rosaria Mita Amalia (University of Muhammadiyah Purwokerto, 2019)
After being recognized as a legitimate form of marriage in various countries, the Supreme Court of the United States ruled that the American Constitution guarantee the marriage of same-sex. It is the syllabus of same-sex Marriage in the United States that become the object of the research. This thesis aims to identify the attitude types and clauses constituent of syllabus constructed by same-sex marriage proposer in the United States and examines how attitude types in the syllabus of Same-sex Marriage in the United States indicates the meaning and relation with the readers. The theory proposed by Martin and White of Appraisal system (2005) based on attitude types is used to support the analysis. The research found that the attitude types in same-sex marriage syllabus there are 92 affect, 54 judgement, and 58 appreciation. Based on the attitudinal types in this research, the same-sex proposers feeling indicates they are being discriminated because their citizenship rights have not been fulfilled. It can be seen from the most choice of the word